Allenic phosphonium borate zwitterions via a phosphonium allenylidene intermediate. Issue 67 (29th July 2021) - Torres, Lucas C.; Dobrovetsky, Roman; Caputo, Christopher B.
Abstract : An unexpected alkynyl phosphane rearrangement with Lewis acids yield a phosphonium borato-allene zwitterion via a transient tricoordinate phosphorus electrophile. Abstract : We describe the synthesis of alkynyl phosphanes of the type R2 P–CC–C(OCH3 )Ph2 (R = Ph, Cy) and investigate their transformation to geminally substituted phosphonium borato-allene zwitterions upon their reaction with B(C6 F5 )3 . The mechanism for this transformation was studied experimentally and by density functional theory computations (DFT), suggesting the intermediacy of an unsaturated 3-coordinate phosphonium electrophile akin to a methylene phosphonium cation.